Tigranakert of Artsakh - Petrosyan, Hamlet (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
Tigranakert of Artsakh is situated in the Askeran region of the Republic of Artsakh (former Nagorno Karabakh Autonomous Region), in the lower valley of Khachenaget, the second-largest river of the highlands. Occupying an area of more than 70 ha, it is spread over the south-western lower slope of Mt Vankasar and in the plain next to it (Figure 1), in the neighbourhood of the freshwater sources called ‘Shahbulagh’ (‘Royal Sources’). The city was founded at the end of 90s BC by the Armenian King, Tigranes II the Great (95-55 BC). The Artsakh expedition of the Institute of Archaeology and Ethnography of the National Academy of Sciences of Armenia found traces of the city in 2005, and thus far has realised archaeological excavations in its vicinity. Tigranakert of Artsakh is the only one among numerous settlements named after Tigranes that has been precisely located and is being investigated by archaeologists. The archaeological museum of the city was founded in 2010, based on the large amount of excavated archaeological material. Tigranakert is the most visited archaeological site in Artsakh, described in detail on the Internet, and is widely known within scientific circles and the public. The investigations of Tigranakert were undertaken and financed by the ‘Yerkir’ Union of Non-Governmental Organisations for Repatriation and Settlement. Since 2008, the archaeological investigation of the site has been financed by the government of the Republic of Artsakh.